Prepose: Privacy, Security, and Reliability for Gesture-Based Programming - , Lucas Silva Figueiredo; Molnar, David; Veanes, Margus; , Benjamin Livshits (IEEE Security & Privacy, 2017)
With the rise of sensors such as Microsoft Kinect, gesture-based interfaces have become practical. However, to recognize such gestures, applications need access to users' depth and video, exposing sensitive data about individuals and their environment. Prepose, a domain-specific language for building gesture recognizers, combined with a system architecture that protects privacy, security, and reliability with untrusted applications, addresses these threats.